1999
DOI: 10.1016/s0377-1237(17)30439-2
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasmas Urealyticum and Human Infertility: Effect on Spermatozoa Morphology

Abstract: Seminal fluids of 197 males with complaints of involuntary infertility were examined for spermatozoal counts, morphological changes in the spermatozoa and cultured for ureaplasmas and mycoplasmas. In 12, no spermatozoa were present, 29 had a count of less than one million and 156 had more than one million spermatozoa per mL of the seminal fluid. Various morphological changes were detected in the spermatozoa in some cases. U urealyticum and M hominis were grown in 43.15% and 16.75% in comparison to control figu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Thirty‐five studies used PCR or culture to isolate specific bacteria, namely Chlamydia trachomatis , Ureaplasma spp. and Mycoplasma spp 9,19,51,52,55,60‐89 . The PCR technique identified C trachomatis in 15 studies with reported prevalence of between 0.3% and 43.3% in infertile men, which is in contrast to the culture technique where this species was not identified in any of the studies (0/20).…”
Section: Evidence Synthesismentioning
confidence: 88%
“…Thirty‐five studies used PCR or culture to isolate specific bacteria, namely Chlamydia trachomatis , Ureaplasma spp. and Mycoplasma spp 9,19,51,52,55,60‐89 . The PCR technique identified C trachomatis in 15 studies with reported prevalence of between 0.3% and 43.3% in infertile men, which is in contrast to the culture technique where this species was not identified in any of the studies (0/20).…”
Section: Evidence Synthesismentioning
confidence: 88%
“…These microbes have been isolated from seminal fluid and known to cause infertility in some cases. Morphological changes due to the spermatozoa infection are coiling of tail and a fuzzy coat around the tail and these have been well demonstrated by Debata et al [5], with specificity rate of 98.2% in culture positive cases. Their identification and treatment has shown positive effect on semen quality [6,7].…”
Section: Microbial Infection As Male Factor In Infertilitymentioning
confidence: 65%
“…In general, the lipopolysaccharide contained in the cell walls of gram-negative bacteria (like Bacteroidia , Sphingobacteria , Proteobacteria , or Alphaproteobacteria ) are suspected to disrupt sperm motility [ 28 ]. Low rates of normal morphology in sperm have been observed in samples with the abundance of Staphylococcus aureus , Ureaplasma urealyiticum , HCMV, and human polyomavirus 2 (JCPyV) [ 34 , 76 , 83 , 84 , 85 ], and low sperm counts have been associated with the presence of Staphylococcus , Haemophilus , Klebsiella , Chlamydia trachomatis , and ZIKV [ 25 , 32 , 56 , 74 , 76 , 82 ]. Patients with azoospermia have shown more abundance of Mycoplasma and Ureaplasma [ 27 ], as well as an increase in Bacteroidetes , Firmicutes [ 86 ], Proteobacteria , and Actinobacteria [ 87 ].…”
Section: The Semen Microbiome In Fertility Disordersmentioning
confidence: 99%
“… The main genera that have been described as potentially associated with high quality ( up ) and low quality ( down ) seminal parameters [ 13 , 21 , 22 , 29 , 32 , 54 , 55 , 56 , 74 , 75 , 76 , 77 , 79 , 80 , 83 ]. …”
Section: The Semen Microbiome In Fertility Disordersmentioning
confidence: 99%
See 1 more Smart Citation